2017
DOI: 10.3389/fped.2017.00048
|View full text |Cite
|
Sign up to set email alerts
|

A Case of 22q11 Deletion Syndrome (22q11DS) with a Panayiotopoulos Epileptic Pattern: Are Additional Copy-Number Variations a Possible Second Hit in Modulating the 22q11DS Phenotype?

Abstract: “22q11 deletion syndrome” (22q11DS) is a rare genetic syndrome, in which most patients share the same deletion, but their clinical features may vary a great deal. The genetic mechanisms underlying the variable expressivity and reduced penetrance of 22q11DS still have to be fully elucidated. Epilepsy has been reported in about 15.2% of the patients; however, few studies have focused on this topic, and in most cases, a detailed epileptic profile is missing. Since only a minority of patients experience epileptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Based on the early onset of PS in these patients and the severity of their symptoms, the authors concluded that mutations in the SCN1A gene may regulate the severity of the syndrome rather than the genesis of the disorder (Martín Del Valle et al, 2011 ). In a very recent study, a 6-year old girl diagnosed with PS was presented with a de novo 2.6 Mb deletion in 22q11.2 and an additional 172 kb duplication in 2q37.1 (Bertini et al, 2017 ). Deletion in 22q11.2 was associated with loss of genes involved in brain function and development, such as RTN4R (reticulon four receptor, NOGO RECEPTOR) (Pan et al, 2005 ; Ramasamy et al, 2014 ), SNAP29 (synaptosomal-associated protein 29) and gene responsible for biogenesis of micro-mRNA, especially in mammalian brain such as DGCR8 (microprocessor complex subunit 8) (Cheng et al, 2014 ).…”
Section: Panayiotopoulos Syndromementioning
confidence: 99%
“…Based on the early onset of PS in these patients and the severity of their symptoms, the authors concluded that mutations in the SCN1A gene may regulate the severity of the syndrome rather than the genesis of the disorder (Martín Del Valle et al, 2011 ). In a very recent study, a 6-year old girl diagnosed with PS was presented with a de novo 2.6 Mb deletion in 22q11.2 and an additional 172 kb duplication in 2q37.1 (Bertini et al, 2017 ). Deletion in 22q11.2 was associated with loss of genes involved in brain function and development, such as RTN4R (reticulon four receptor, NOGO RECEPTOR) (Pan et al, 2005 ; Ramasamy et al, 2014 ), SNAP29 (synaptosomal-associated protein 29) and gene responsible for biogenesis of micro-mRNA, especially in mammalian brain such as DGCR8 (microprocessor complex subunit 8) (Cheng et al, 2014 ).…”
Section: Panayiotopoulos Syndromementioning
confidence: 99%
“…Nevertheless, the genetic architecture for occipital SLCE is still not completely understood [ 2 ]. Oligogenic inheritance has been proposed for SLCEs, complicating the recognition of etiological genetic abnormalities in single-family studies [ 31 ]. It is important to emphasize that our studies were not designed to functionally prove a pathogenic role of the discovered FGD6 variant [ 32 ].…”
Section: Discussionmentioning
confidence: 99%